Development of a New Validated Stability Indicating RP-HPLC Method for the Determination of Irbesartan and Hydrochlorothiazide - Srinivasu, Topalli (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Irbesartan (IRB) is an angiotensin receptor blocker used mainly for the treatment of hypertension. Hydrochlorothiazide (HCTZ) is a first-line diuretic drug of thiazide class which acts by lowering the blood pressure initially by increasing sodium and water excretion. A simple, precise, accurate, and robust stability-indicating liquid chromatographic method (gradient mode) was developed and validated for the simultaneous determination of IRB and HCTZ in pharmaceutical dosage forms (Tablets). Materials and Methods: Chromatographic separation was achieved on an X Bridge shield RP C-18 (150 mm × 3.0 mm, 3.5 μm) column of Waters high-performance liquid chromatography with Empower2 software and photodiode array detector, maintained at 45°C using 0.1% v/v formic acid:acetonitrile (40:60, v/v), with flow rate 0.8 ml/min (ultraviolet detection at 235 nm). Results and Discussion: HCTZ and IRB obey Beer–Lambert’s law over the concentration range of 2–600 μg/ml and 1.2–560 μg/ml, respectively, with regression equations y = 10669x −2468 (HCTZ) (R2 = 0.9999) and y = 18222x + 18180 (IRB) (R2 = 0.9997). The limit of quantification (LOQ) and limit of detection (LOD) for IRB were found to be 1.056 μg/ml and 0.349 μg/ml, respectively, whereas the LOQ and LOD for HCTZ were found to be 1.980 μg/ml and 0.654 μg/ml, respectively. IRB and HCTZ were subjected to stress conditions of acidic, alkaline, and oxidation degradations. The forced degradation studies were performed using HCl, NaOH, and H2O2. Conclusions: HCTZ and IRB are slightly sensitive toward alkaline conditions in comparison to other degradations. The method was validated as per ICH guidelines.